Flexible random lasers in dye-doped bio-degradable cellulose nanocrystalline needles - Germano, Gleice C. M. (2021)
M-ERA-NET2/0007/2016 POCI-01-0145-FEDER-007688 PTDC/CTM-BIO/6178/2014 PTDC/CTM-REF/30529/2017 UID/CTM/50025